CONTEMPORARY MIGRATIONS FROM THE PERSPECTIVE OF HUMAN SECURITY PARADIGM (Security Dialogues, 2024)
The paper considers migrations from the perspective of human security paradigm, with special focus on the Post World War II period. Even though the initial activities in establishing the concept of human security have been taken in mid-40s of the last century under the umbrella of United Nations, its affirmation in scientific and political circles is reached only in the aftermath of the Cold War era, when significant steps forward were madeto extend the security agenda to non-military threats and other referent objects of security, outside the previously dominant state-centric approach. This is a concept that embodies the idea of multidimensional approach to security, which places human being and his daily exposure to different threats and disturbances that represent an existential threat in the center of scientific observations, making it indispensable in considering the contemporary migratory movements, especially multiple factors that affect them. A special focus of the paper is on determining the migration-related problems through the prism of two fundamental components of human security – freedom from fear (freedom from violence, oppression and persecution) and freedom from want (freedom from poverty, penury and misery), the insufficiency of which is accounted in certain parts of the world as a significant factor in making the decision to emigrate from country of origin.
Keywords: human security, migrations, conflicts, persecution, poverty, Global South